Evolution of Vanadium Redox Flow Battery in Electrode - Md Hasnat, Hossain; Norulsamani, Abdullah *; Tan, Kim Han *; Saidur, Rahman *; Mohd Amran, Mohd Radzi; Suhaidi, Shafie (John Wiley & Sons, 2023)
The vanadium redox flow battery (VRFB) is a highly regarded technology for large-scale energy storage due to its outstanding features, such as scalability, efficiency, long lifespan, and site independence. This paper provides a comprehensive analysis of its performance in carbon-based electrodes, along with a comprehensive review of the system‘s principles and mechanisms. It discusses potential applications, recent industrial involvement, and economic factors associated with VRFB technology. The study also covers the latest advancements in VRFB electrodes, including electrode surface modification and electrocatalyst materials, and highlights their effects on the VRFB system‘s performance. Additionally, the potential of two-dimensional material MXene to enhance electrode performance is evaluated, and the author concludes that MXenes offer significant advantages for use in high-power VRFB at a low cost. Finally, the paper reviews the challenges and future development of VRFB technology.